Critical exponents and universality for the isotropic-nematic phase transition in a system of self-assembled rigid rods on a lattice - López, Luis Gonzalo (2009)
Monte Carlo simulations have been carried out for a system of monomers on square lattices that, by decreasing temperature or increasing density, polymerize reversibly into chains with two allowed directions and, at the same time, undergo a continuous isotropic-nematic (IN) transition. The results show that the self-assembly process affects the nature of the transition. Thus, the calculation of the critical exponents and the behavior of Binder cumulants indicate that the universality class of the IN transition changes from two-dimensional Ising-type for monodisperse rods without self-assembly to q=1 Potts-type for self-assembled rods.